KEEFEKTIFAN MODEL GUIDED DISCOVERY LEARNING UNTUK MENINGKATKAN KETERAMPILAN KETERAMPILAN BERPIKIR KRITIS - Dian Noer Asyari (Edupedia : Jurnal Studi Pendidikan dan Pedagogi Islam, 2019)
Discovery learning is a learning situation on wich the principle content of what is tobe learned is not give but must be independly discovered by student. The effectiveness of guided discovery learning model to improve students’ critical thinking skills uses 6 indicators, are: formulating problems, formulating hypotheses, analyzing date, providing alternatives, summing up, communicating and applying principle. The guided discovery learning model was included in the effective category in terms of: (a) Improvement (N-gain) of students’ critical thinking skills by 0.65 with moderate criteria and (b) Students respond positively to learning using guided discovery learning model and its learning tools on implementation.